Pendidikan Agama Kristen Dalam Keluarga: Pengembangan Nilai Mealtable Sharing Terhadap Keharmonisan Hubungan Kasih Antara Orang Tua dan Anak Di Jemaat Gmim Bukit Sion Mapanget - Farly Rolando Roringpandey; Netanel Kaunang; Semuel Selanno (Pascasarjana IAKN Manado, 2022)
The purpose of this study is to describe and analyze the development of the values ​​contained in Mealtable Sharing related to the value of harmony in the family, the process of developing the value of mealtable sharing in the GMIM Bukit Sion Mapanget Congregation in relation to the harmonious relationship of love between parents and children, Inhibiting factors in the process of developing the Value of Mealtable Sharing on the Harmony of Love Relationships between Parents and Children in the GMIM Bukit Sion Mapanget Congregation, and the efforts made by parents and Church leaders in overcoming the inhibiting factors related to the development of the Value of Mealtable Sharing on Harmony The Relationship of Love between Parents and Children in the GMIM Bukit Zion Mapanget Congregation. This research method is a descriptive qualitative research conducted at the GMIM Bukit Sion Mapanget Congregation. Data were collected through observation, interviews and documentation studies. From the results of the analysis and interpretation of the data obtained that: (1). Eating together and talking together